Assessment of antioxidant activity and total polyphenol in avena sativa from arequipa city - Cesar Augusto Roque Borda (2017)
The Avena sativa, a food that besides offering the basic requirements in the diet provides additional benefits towards the health, preparing diseases chronically degenerative as: obesity, diabetes, cardiovascular and cancer. The aim of this work was to determine the profile of polyphenols of the ethanolic extract of oats by means of HPLC and to evaluate the antirust activity by means of the tests beta-carotene/linoleic acid, test FRAP, inhibition of the radical DPPH• and the total present polyphenols for the test Folin-Ciocalteau. The results provide a preliminary basis for further exploitation of this plant and its chemical components and application development.